Punishing the homeless: The constitutionality of the criminalisation of homelessness in the City of Cape Town - Nogwavu, Lelethu Sisakazi (Department of Public Law, 2023)
This research is a doctrinal study into Section 2(2), read with section 23, of the City of Cape Town's Streets Public Places and the Prevention of Nuisances By-law of 2007 and whether it violates the right to human dignity entrenched in section 10 of the Constitution. The provision prohibits begging, sitting, standing and lying in public places in the City of Cape Town. The overall argument made in this dissertation is that this prohibition is unconstitutional for the following three reasons: Firstly, it unlawfully interferes with homeless peoples efforts to maintain and build and decent life. Secondly, it disproportionally discriminates against black people. Lastly, it halts transformation in South Africa. Upon the findings of its analysis, this study aims to make recommendations and suggestions to improve the protection of homeless people in South Africa.